Improved sphere decoding algorithm based on ±1 quadratic programming - LI Zi1; CAI Yue-ming1 (Tongxin xuebao)
With the ±1 quadratic programming of the MIMO detection,the necessary conditions for MIMO detection op-timal solution were derived.An improved sphere decoding algorithm based on these necessary conditions was proposed.The algorithm prunes redundant nodes by necessary conditions based on the origin sphere decoding.With this pruning strategy,the complexity of algorithm is reduced significantly,while holding the bit error rate performance.